Theory-driven development of a mobile phone supported intervention for adolescents with perinatal depression (2021)
Purpose This paper describes the design of a theory-informed pragmatic intervention for adolescent perinatal depression in primary care in Nigeria. Methods We conducted Focus Group Discussions (FGDs) among 17 adolescent mothers and 25 maternal health care providers with experience in the receipt and provision of care for perinatal depression. The Consolidated Framework for Implementation Research (CFIR) was used to systematically examine the barriers and facilitators affecting adolescent mothers' use of an existing intervention package for depression. The Theoretical Domain Framework (TDF) and the Capability, Opportunity, Motivation, Behaviour (COM-B) model were used to analyze the results of the data across the five CFIR domains. Results FGD analysis revealed that care providers lacked knowledge on approaches to engage young mothers in treatment. Young mothers had poor treatment engagement, low social support, and little interest in parenting. A main characteristic of the newly designed intervention is the inclusion of age-appropriate psychoeducation supported with weekly mobile phone calls, to address treatment engagement and parenting behaviours of young mothers. Also in the outer setting, low social support from relatives was addressed with education, “as need arises” phone calls, and the involvement of "neighborhood mothers”. In the inner settings, care providers’ behaviour is addressed with training to increase their capacity to engage young mothers in treatment. Conclusion A theory-based approach helped develop an age-appropriate intervention package targeting depression and parenting skills deficit among perinatal adolescents in primary maternal care and in which a pragmatic use of mobile phone was key.